(untitled) (Journal of Management and Business Education, 2022)
In March 2020, the students of the Master’s Degree in Financial Advice and Planning (MAPF) at the Rey Juan Carlos University suffered the uncertainty of how the health security restrictions that had to be adopted due to the irruption would affect their academic performance of COVID-19 in Spain. In this study, the evolution of the time series of the success rates of all subjects of this master’s degree has been analyzed, taking a study period that begins in normal times and ends after these last two courses affected by COVID-19. The results show that the academic performance of the students in the last two years has not been worse at all, even observing an improvement in the academic performance of the students in the online mode. This can only be interpreted as a success for the university, teachers and students in the face of the challenge posed by the emergence of COVID-19 and the adaptation of teaching.